(untitled) (Research, Society and Development, 2022)
Essential oils are strong antimicrobial candidates with low cost, less toxicity, accessibility, and functionality to circumvent the phenomenon of increasing dissemination of resistant strains of microorganisms. The main objective of the research was to evaluate the sensitivity profile of the bacteria Klebsiella pneumoniae, Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus through the use of essential oils. It was an experimental study with a quantitative approach of the antimicrobial action of essential oils against ATCC bacterial strains, obtained commercially. The selection of essential oils was carried out through the recommendations of the Brazilian Pharmacopoeia. The strains were kept in successive repetitions in Tryptic Soy Aga culture medium, until used in the susceptibility tests. The antifungal activity of the essential oils was performed by the technique of diffusion in agar in wells. It was found that the essential oils of C. cassia, M. Alternifolia and E. caryophyllus were able to sensitize all bacterial strains, with emphasis on greater effectiveness for C. cassia against the species S. aureus with an inhibition halo of 32 mm and M. alternifolia on K. pneumoniae with an inhibition halo of 30mm. E. coli and P. aeruginosa bacteria showed resistance to E. globulus. This study intends to contribute to the increase in the knowledge of the antimicrobial susceptibility profile of essential oils applied in the fight against infectious diseases. Further studies are suggested to identify other essential oils and their phytoconstituents with antimicrobial action.